THE INFLUENCE OF GOOD CORPORATE GOVERNANCE ON THE PROFITABILITY OF COMPANIES LISTED ON GCG AWARD - Nofia Enjelina Sianturi; pelina marbun; Sumita Dewi Manalu; Munawarah . (JASS (Journal of Accounting for Sustainable Society), 2020)
This research is intended to determine the effect of Good Corporate Governance on the profitability of a company in Indonesia. This research is based on a proxy for Good Corporate Governance (GCG), which is the size of an independent commissioner, management of ownership and institutional ownership. Company profitability is proxy by using Return On Equity (ROE) as the dependent variable. The sample in this study are companies registered in the Good Corporate Governance Award in 2016-2018. The method of taking research samples is by purposive sampling, so that the samples are 47 companies in the Good Corporate Governance Award in 2016-2018. Provisional estimates in this study were tested using multiple linear regressions. The results in this study indicate partially in dependent commissioners, management of ownership, institutional ownership, Have no significant effect on profitability. Whereas simultaneously independent commissioners,ownership management, institusional ownership have no effect and are not significant to profitability. Keywords: Good Corporate Governance, Independent Commissioner size, Ownership Management, Institutionals Ownership, and Return On Equity (ROE).